The Need for Public-Private Partnership in Resource Provision and Management for Secondary School Effectiveness in Awka Education Zone - Onuorah, H.C.; Eziamaka, Chika Nonye; Eziechi , Modesta (International Journal of Educational Management, 2021)
The study examined the need of public-private partnership in resources provision and management for secondary school effectiveness in Awka Education Zone. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. The descriptive research design was adopted for the study. The population of the study comprised 548 principals and teachers in the 61 public secondary schools in Awka Education Zone of Anambra State. Through stratified random sampling, the researcher sampled 50% of teachers in the Zone. The instrument of data collection was a structured questionnaire which was developed by the researcher and validated by three experts in education. Mean standard deviation and t-test was used to analyze data for the study. Finding of the study revealed that the role of public private partnership in the provision and management of school resources for school effectiveness include providing physical facilities, recruitment of qualified teachers, providing ICT hardware and software, providing technical support, providing free internet access to school staff and construction of quality convenience for students and staff among others. Furthermore, the respondents' years of experience did not significantly influence their opinion. Based on these findings, the researcher recommended that a national framework and implementation plan for the integration of Public Private Partnerships for the Management of public secondary schools in Nigeria should be set up by the Federal Ministry of Education.